2017
DOI: 10.1016/j.jval.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Thresholds in Global Health: Taking a Multisectoral Perspective

Abstract: Good health is a function of a range of biological, environmental, behavioral, and social factors. The consumption of quality health care services is therefore only a part of how good health is produced. Although few would argue with this, the economic framework used to allocate resources to optimize population health is applied in a way that constrains the analyst and the decision maker to health care services. This approach risks missing two critical issues: 1) multiple sectors contribute to health gain and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 38 publications
0
49
0
2
Order By: Relevance
“…The alternatives should be allocated until the limit of the health budget. The Cost-Effectiveness Ratio (CER, inverse of the ECR) of the last funded technology corresponds to the CET [22,29,51].…”
Section: The Opportunity Costs Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The alternatives should be allocated until the limit of the health budget. The Cost-Effectiveness Ratio (CER, inverse of the ECR) of the last funded technology corresponds to the CET [22,29,51].…”
Section: The Opportunity Costs Methodsmentioning
confidence: 99%
“…Despite the economic evaluations being a mandatory part of the process of HTA in many countries, such as Brazil, USA, Canada and Australia, an explicit CET value has never been established for the assessment of new technologies in their national health systems [19,20,21]. Many countries do not specify a threshold arguing that the benefits of doing so are controversial [5,14,15,16,18,22,23,24,25]. It has been suggested that the use of an explicit threshold could give manufacturers an incentive to "bid up" their price to the ICER level and that it could adversely affect the flexibility of decision makers, although there is little evidence of the latter [7,13,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The US Panel also advocates the use of a 'societal' perspective, which entails incorporating additional costs into CEA beyond those in the healthcare sector; for example, costs of informal care and lost productivity [26]. The way in which costs from different sectors can be aggregated for use in this perspective is also debated in emerging literature [27,28]. Finally, irrespective of perspective, there are questions relating to which types of costs should be incorporated within economic evaluations; for example, if sunk and fixed costs should be included.…”
Section: What Costs To Include: a Brief Introduction To Costing Perspmentioning
confidence: 99%
“…Commission on Macroeconomics and Health, 2001;Marseille et al, 2015;Bertram et al, 2016; Paulden et al, 2016;Pinto et al, 2016;. Mais recentemente descritos, os modelos de "estante de livros" (Culyer, 2016;Remme et al, 2016), fronteira de eficiência (Institute for Quality and Efficiency in Health Care, 2009) e eficiência média do sistema (Claxton et al, 2015;Woods et al, 2016) são alternativas ao uso de valores fixos de LCE.Sob uma perspectiva de custo de oportunidade, como o LCE indica aquelas tecnologias que são eficientes para incorporação, não é possível que o orçamento e o limiar sejam simultaneamente fixos. A ideia de implantação do princípio de custo de oportunidade é que, para a incorporação de novas tecnologias que impõe custos adicionais ao sistema, em um contexto de escassez de recursos, haverá deslocamento de tecnologias financiadas ou que esse recurso faltará em algum outro ponto do sistema.…”
unclassified
“…Commission on Macroeconomics and Health, 2001;Marseille et al, 2015;Bertram et al, 2016;Paulden et al, 2016;Pinto et al, 2016;. Mais recentemente descritos, os modelos de "estante de livros" (Culyer, 2016;Remme et al, 2016), fronteira de eficiência (Institute for Quality and Efficiency in Health Care, 2009) e eficiência média do sistema (Claxton et al, 2015;Woods et al, 2016) são alternativas ao uso de valores fixos de LCE.…”
unclassified